THE TRANSLATION OF THE QUR’AN IN SAMBAS SCRIPT: A STUDI ON JAWI AND LATIN SCRIPT BY MUHAMMAD BASIUNI IMRAN - Herlambang, Saifuddin; Kadir Naffati, Abdel; Nurmansyah, Ihsan; Kurnia Oktaviana, Sherli (Jurnal Lektur Keagamaan, 2023)
ABSTRACT This article presents a study examining the use of Jawi and Latin scripts in Muhammad Basiuni Imran's Quran tafseer (commentary) in Sambas. The study employed historical research, where the data was collected through literature study. The results of this study suggest that the use of Jawi and Latin script was related to the different backgrounds of reader segmentation as well as Muhammad Basiuni Imran's stance towards Dutch colonialism. In practical terms, Tafsir Tujuh Surah and Ayat as-Siyam, written in Jawi script, were explicitly written for the Malay community in the Sambas Sultanate, who were only able to read Jawi. On the other hand, al-Ibanatoe wal Inshafoe, written in Latin script, was intended for a wider Indonesian audience, who were able to read Latin script. The choice of script also influenced the thematic content of Muhammad Basiuni Imran's Quranic tafseer. The Tafsir Tujuh Surah and Ayat as-Siyam, composed in Jawi script, were primarily characterized by explanations of well-known verses and surahs that are routinely recited during prayers, thereby necessitating their comprehension by the Malay community within the Sambas Sultanate. On the other hand, al-Ibanatoe wal Inshafoe, written in Latin script, predominantly contained explanations on the contemporary conflicts and debates within the Malay and Indonesian Muslim communities over religious issues. This was designed to facilitate a wider comprehension among the general populace, thereby fostering unity within the Muslim community. From an academic perspective, the utilization of these two scripts indicates Muhammad Basiuni Imran's moderate stance, embodying a symbolic form of resistance against Dutch colonialism. This study further reinforces the concept of religious moderation in Indonesia, specifically via the usage of Jawi and Latin script in Muhammad Basiuni Imran's tafseer in Sambas. Keywords: Jawi script, Latin script, Quranic Commentary, Muhammad Basiuni Imran   ABSTRAK Tujuan penulisan artikel ini adalah untuk mengkaji penggunaan aksara Jawi dan Latin dalam karya tafsir Muhammad Basiuni Imran di Sambas. Metode penelitian yang digunakan adalah metode penelitian sejarah, dengan teknik pengumpulan data yang digunakan adalah studi pustaka. Hasil penelitian menunjukkan bahwa penggunaan aksara Jawi dan Latin berkaitan erat dengan konteks segmentasi pembaca yang berbeda serta sikap Muhammad Basiuni Imran terhadap kolonial Belanda. Secara praktis, TafsirTujuh Surah dan Ayat as-Siyam ditulis untuk masyarakat Melayu di Kesultanan Sambas yang umumnya hanya mampu membaca aksara Jawi, sedangkan al-Ibanatoe wal Inshafoe ditulis untuk masyarakat Indonesia secara lebih luas yang mampu membaca aksara Latin. Penggunaan kedua aksara tersebut berimplikasi pada perbedaan substansi penafsiran Muhammad Basiuni Imran terhadap ayat al-Qur’an. Tafsir Tujuh Surah dan Ayat as-Siyam yang beraksara Jawi lebih dominan berisi penjelasan tentang ayat dan surah yang sudah familiar dan selalu dibaca dalam shalat, sehingga harus dihayati dan dipahami oleh masyarakat Melayu di Kesultanan Sambas. Sementara itu, al-Ibanatoe wal Inshafoe yang beraksara Latin didominasi penjelasan tentang masyarakat Muslim di tanah Melayu dan Indonesia yang sedang berselisih dan berbantah-bantahan dalam perkara agama sehingga harus dipahami oleh masyarakat secara umum untuk mendorong persatuan umat Islam. Secara akademis, penggunaan kedua aksara tersebut sebagai bentuk sikap moderat Muhammad Basiuni Imran dalam upaya perlawanan simbolis terhadap kolonial Belanda. Kajian ini memperkuat moderasi beragama di Indonesia, khususnya melalui penggunaan aksara Jawi dan Latin dalam karya tafsir Muhammad Basiuni Imran di Sambas.  Kata kunci: Aksara Jawi, Aksara Latin, Tafsir al-Qur’an, Muhammad Basiuni Imran